Evaluation of association between methylenetetrahydrofolate reductase and azoospermia: Retraction. Issue 15 (16th April 2021) - Tan, Guang-Xing; Jiang, Lin; Li, Gang-Qin; Bai, Kuan
Abstract: Background: Infertility affects childbearing age couples all over the world. One of the important reasons for infertility is genetic factors. Our study evaluated the association between methylenetetrahydrofolate reductase (MTHFR) and azoospermia. Methods: Multiple databases like MEDLINE, EMBASE, Cochrane library, and China journal full-text database were used to search for relevant studies, and full-text articles involved in the evaluation of MTHFR and azoospermia. The results were evaluated using STATA 12.0. Heterogeneity analysis, sensitivity analysis, and bias analysis were also performed on the data. Results: Thirteen related studies eventually met the inclusion criteria. Significant association between C677T polymorphism and azoospermia (relative risk [RR] = 0.94 [0.90, 0.99], I 2  = 60.9%, P  = .002), and between A1298C polymorphism and azoospermia (RR = 0.98 [0.94, 1.02], I 2  = 56.3%, P  = .011) was observed. Meanwhile, in subgroup analysis, Caucasians had higher risk than Mongolians in association between MTHFR and azoospermia. Conclusion: There was association between MTHFR polymorphism and azoospermia. Caucasian populations had higher risk than Mongolian populations in association between MTHFR and azoospermia.